Pilon Fracture Management: Distal Tibial Locking Plate Vs Ilizarov - Tahir, Muhammad Awais; Ahmed, Rana Dawood; Hassan, Allah Rakha; Ahmed, Shaharyar; Khalid, Haidar Ali; Khandan, Ajmal (Indus Journal of Bioscience Research, 2025)
Introduction: Several methods have been used to treat tibial pilon fractures, while the best course of action is still up for debate. In order to restore the distal fibula length and articular surface, these patients are typically treated in Europe with open reduction and internal fixation of the tibia, with bone grafting as needed. Study design: Randomized Controlled trial. Settings: Department of Orthopedic Surgery, Allied Hospital, Faisalabad. Study duration: November 2024 and February 2025. Materials and Procedures: 256 patients (128 in each group) of either gender, aged 18 to 50, who presented with Anderson grade 1 traumatic extra-articular/intra-articular distal tibial fractures were chosen. Patients with compartment syndrome, generalized bone or joint disease, pathological fractures, uncontrolled diabetes mellitus, peripheral vascular disease, other significant injuries or polytrauma, and prior surgery were excluded. The patients were split into two groups at random using the lottery method. Group A were undergone tibial locking plate and group B were undergone ilizarov technique. The lower extremity functional score (LEFS), as described by the patient, is the main result. The functional score for the lower extremities ranges from 0 to 80 points. Results: Patients in groups A and B had mean ages of 36.17 ± 8.33 and 37.02 ± 7.16 years, respectively. With a male to female ratio of 2.5:1, 182 (71.09%) patients were males and 74 (28.91%) were females. The mean LEFS score at 12 weeks was 61.80 ± 4.55 for group A and 64.66 ± 5.24 for group B (p-value = 0.0001). Conclusion: In comparison to ilizarov technique, this study found that tibial locking plate offers superior lower extremity function score.